Post-duodenal polypectomy pancreatitis: an uncommon iatrogenic trigger - Gonzalez Mosquera, Daniel A.; Menghrajani, Rajiv Hans; Mateo Chavez, Maria B.; Banks, Marcus; Kilani, Yassine (International Journal of Research in Medical Sciences, 2025)
Acute pancreatitis (AP) is a major cause of gastrointestinal-related admission in the United States, characterized by epigastric pain radiating to the back, and nausea and vomiting. Although commonly associated with alcohol consumption and gallstones, cases involving less frequent triggers, such as post-endoscopy, have been reported. We present an unusual case of post-polypectomy pancreatitis following esophagogastroduodenoscopy (EGD). A 20-year-old woman underwent polypectomy during a bariatric EGD screening procedure, resulting in a 2 mm non-bleeding pedunculated polyp’s polypectomy from the second part of the duodenum. She experienced excruciating abdominal pain, nausea, and vomiting within an hour. Following an emergency evaluation, the diagnosis of acute pancreatitis was made; this was supported by increased lipase enzyme and physical manifestation. While AP tends to be triggered by well-known reasons, this particular case highlights a distinctive iatrogenic trigger-duodenal polypectomy. Only a handful of similar cases have been documented. The duodenum’s peculiar proximity to important pancreatic structures may result in mechanical injury or heat-induced pancreatic damage. The management, similar to typical acute pancreatitis care, underscores the importance of supportive measures. This rare case of post-polypectomy pancreatitis emphasizes the risk of iatrogenic complications. Timely diagnosis and surveillance following procedures involving the duodenum can help with early diagnosis.